Effectiveness of the implementation of the rice farming insurance program in Deli Serdang regency: An Islamic perspective - Muhammad Bima Nugraha; Nurul Inayah; Muhammad Ikhsan Harahap (LPMP Imperium, 2026)
This study analyzes the effectiveness of the Rice Farming Insurance Program (AUTP) in Durian Village, Deli Serdang Regency, from an Islamic economics perspective. Using a qualitative descriptive approach and purposive sampling of ten informants, including farmers and agricultural extension workers, data were gathered through interviews, observations, and documentation. The findings indicate that AUTP's effectiveness is hindered by issues such as target accuracy, limited program awareness, and inadequate monitoring. Many tenant farmers are excluded due to administrative requirements, while uneven information dissemination and delayed claim settlements diminish the value of compensation. These challenges suggest that AUTP does not fully embody the Islamic principles of justice, mutual assistance, public welfare, and the protection of wealth, life, and intellect. This study integrates program effectiveness analysis with Islamic economic principles, providing a useful framework for improving agricultural insurance policies to protect vulnerable farmers better. Public Interest Statement: The findings highlight that unequal access to information, technological barriers, and delays in claim disbursement hinder the effectiveness of agricultural insurance programs. The study calls for more inclusive policies, simplified procedures, and stronger institutional support. It also stresses integrating Islamic economic values such as justice, mutual assistance, public welfare, and wealth protection into these policies. Ultimately, the research aims to enhance farmer welfare, bolster rural resilience, and promote sustainable agricultural development in Indonesia.